HERMETICITY OF COTTON PNEUMOTRANSPORT PIPELINES, ITS INFLUENCE ON PERFORMANCE AND ENERGY CONSUMPTION (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article examines the importance of connecting pneumatic transport pipes in cotton ginning plants. The impact of air duct sealing on fan performance and energy consumption is considered.